Feto‐maternal heart rate ratio in pregnant bitches: effect of gestational age and maternal size. (20th July 2016) - Alonge, S; Mauri, M; Faustini, M; Luvoni, GC
Contents: Few information is available on parameters that can be used to objectively assess the foetal health during canine pregnancy. To identify a reliable parameter for the evaluation of foetal well‐being, the effect of pre‐gestational maternal bodyweight and gestational age on foetal heart rate (FHR) and on feto‐maternal heart rate ratio (FHR/MHR) was investigated. Seventeen client‐owned pregnant bitches of different pre‐gestational maternal bodyweight were examined by serial echo colour Doppler. Only data from 11 uncomplicated pregnancies were included in the statistical analysis. The relationship between FHR, and FHR/MHR, and independent variables was analysed by polynomial regression ( p  ≤ .05). The FHR and the FHR/MHR significantly fitted a multiple quadratic regression for all independent variables. They both increased from 35 to 20 days before parturition and then a decreasing pattern followed. Higher values of both parameters were observed in bitches of lowest and highest bodyweight. Patterns of FHR and FHR/MHR were similar, but the ratio better describes the effect of the independent variables on the data. Thus, the highest significance of FHR/MHR compared to FHR alone encourages the application of this ratio to evaluate foetal well‐being. The equation derived by the regression analysis of FHR/MHR could be applied in clinical practice to obtain its expected values in healthy pregnancies.